Analisis Wacana Kritis Bahasa Dakwah Persuasi Postingan Instagram Ustadz Felix Siauw (@Felixsiauw) - Ula, Saidatul; Simpen, I Wayan; Evi W. Citrawati, Ni Putu (Stilistika : Journal of Indonesian Language and Literature, 2021)
This research is about the analysis of da'wah language. Da'wah is an activity to invite others to believe and obey Allah SWT for Muslims. With the development of social media, da'wah is not only carried out in mosques or prayer rooms, but can be done through various social media, and one of them is Instagram. Ustadz Felix Siauw is one of the Ustadz who uses Instagram social media in preaching. The purpose of this study is to determine the lingual characteristics of Ustadz Felix Siauw's da'wah language seen from its superstructure, macrostructure, and microstructure. This study uses the agih method with the analytical technique of Van Dijk. The results of this study indicate that Ustadz Felix Siauw's Instagram post from January-December 2019 has a superstructure in the form of a title as the opening text. In its macrostructure, there is an intention to invite Indonesian Muslims to know more about Islam and put God first. Microstructure by analyzing based on semantics, syntax, stylistics, and rhetoric, and based on its microstructure, Ustadz Felix's preaching discourse from January-December has a lingual characteristic of rhetorical language style in its delivery.